Factors associated with follow‐up attendance of patients with oral squamous cell carcinoma: A retrospective cohort study. Issue 4 (24th February 2023) - Wang, Shun‐Ji; Lin, Bo; Shen, Shi‐Yue; Lin, Jian‐Lin; Zhang, Tian‐Wen; Yang, Hong‐Yu
Abstract: Background: This study examined the postoperative follow‐up attendance of oral squamous cell carcinoma (OSCC) patients, evaluated some of the factors associated with it, and assessed its relationship with early detection of postoperative disease progression. Methods: An exploratory retrospective cohort study of 430 OSCC patients was conducted. We examined associations of follow‐up attendance within the first year after surgery with selected demographic and clinical factors, and with early detection of disease progression. Results: The mean number of follow‐up visits within the first year after surgery was 3.9 out of the 12 recommended at our center; few patients were fully adherent. Age ≥70 years, unmarried status, high education level, and negative history of surgery for premalignant or malignant lesions from oral cavity or other sites were significantly associated with lower follow‐up attendance. Greater follow‐up attendance was significantly associated with early detection of disease progression during the first year after surgery ( p  = 0.025). Conclusions: Adherence to follow‐up visits was poor. Several sociodemographic and clinical factors were related to follow‐up attendance, greater follow‐up attendance was significantly associated with early detection of disease progression, and these should be further explored in future research.